A Biomechanical Comparison of Four Hip Arthroplasty Designs in a Canine Model - Ordway, Nathaniel R.; Ash, Kristian J.; Miller, Mark A.; Mann, Kenneth A.; Hayashi, Kei (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to develop an in vitro biomechanical protocol for canine cementless hip arthroplasty that represents physiological gait loading (compression and torsion) and to evaluate if three alternative implant designs improve fixation compared with the traditional collarless, tapered stem in the clinically challenging case of moderate canal flare index.Study Design Twenty-four (six/group) laboratory-prepared canine constructs were tested using a simulated gait and overload (failure) protocol. Construct stiffness, failure load/displacement and migration were measured as outcome variables.Results Simulated gait loading did not show any significant differences between implant types for peak displacement, peak rotation, torsional stiffness, subsidence or inducible displacement. The collared and collarless stem groups were stiffer in compression compared with the collarless with a lateral bolt and short-stem groups. Increasing the loading above simulated gait showed significant reductions in compressive and torsional stiffness for all implant constructs. Despite the reductions, the short-stem group showed significantly higher stiffness compared with the other three groups.Conclusion Peak failure loads (compressive and torsional) in this study were approximately four to seven times the simulated gait loading (430 N, 1.6 Nm) regardless of implant type and highlight the importance of limiting activity level (trotting, jumping) following hip replacement in the postoperative period and during the osseointegration of the implant.
Keywords: hip; arthroplasty; implant fixation; biomechanical performance of implants; gait mechanics; simulated gait loading; dogs